2003
DOI: 10.1007/s00122-003-1321-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a secondary grapevine domestication centre detected by SSR analysis

Abstract: The origin of the grapevine was investigated with archaeobotanical, cultural and historical data. A primary domestication centre was located in the Near East region but there is no agreement on the existence or role of secondary domestication centres. In this work, PCR-based microsatellite analysis has been applied to study the origin of some Italian cultivated grapevines from in situ direct domestication of the wild autoctonous grapevine. Three different Italian locations in Grosseto, Cosenza and Nuoro were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
113
4
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(138 citation statements)
references
References 16 publications
17
113
4
4
Order By: Relevance
“…S2). These results are in agreement with previous studies showing no reduction in genetic diversity in vinifera compared with its wild ancestor (22,23,25,26) and with the relatively minor changes in morphology observed between sylvestris and vinifera (11). A recent study found a significant increase in LD in vinifera compared with sylvestris using 36 microsatellites, however (26).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…S2). These results are in agreement with previous studies showing no reduction in genetic diversity in vinifera compared with its wild ancestor (22,23,25,26) and with the relatively minor changes in morphology observed between sylvestris and vinifera (11). A recent study found a significant increase in LD in vinifera compared with sylvestris using 36 microsatellites, however (26).…”
Section: Discussionsupporting
confidence: 93%
“…4 and Table 1). Grape growing and winemaking then expanded westward toward Europe, but the degree to which local wild sylvestris from Western Europe contributed genetically to Western European vinifera cultivars remains a contentious issue (1,(22)(23)(24). Our results, based on Fst (Table 1), PCA (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The results obtained reinforced the idea of Western Europe as one of the domestication centres for grapevines (Grassi et al 2003, Arroyo-Garcia et al 2006, with contributions from the Eastern gene pool (Imazio et al 2006). The observed genetic structure is a starting point to clarify the high number of native cultivars from Portugal, and it reinforces their probable origins on the Iberian Peninsula.…”
Section: S55supporting
confidence: 84%
“…Nevertheless, specific soil and climatic conditions in new regions where grapevine began to grow influenced and extended its genetic variation. Secondary domestication events, such as mutations, occurred [1] to create new genetic variants within clones derived from vegetatively propagated single plants [2]. Consequently, this process was frequently associated with synonymies and homonymies in the names of cultivars and clones.…”
Section: Introductionmentioning
confidence: 99%